Rationales and practices for dynamic stakeholder engagement and disengagement. Evidence from dementia-friendly health and social care environments. Issue 7 (2nd July 2020) - Pascale, Federica; Pantzartzis, Efthimia; Krystallis, Ilias; Price, Andrew D. F.
Abstract: Latest developments in stakeholder management literature focus on dynamic stakeholder engagement and disengagement practices, and how these are facilitated towards reaching systemic outcomes. However, limited evidence support that this network-level approach can positively influence project success. The paper analyses this issue by considering the practices ( how and when ), rationales ( why ) and outcomes ( so what ) that evolve in the dynamic management of external stakeholders in dementia-friendly environments. This is a crucial area to explore as the ageing population and rising dementia prevalence has increased the need to engage external stakeholders, such as people living with dementia, to develop dementia-friendly health and social environments. The empirical study of the 2013/2014 Department of Health National Dementia Capital Investment Programme involved a statistical and qualitative analysis of 98 pilot projects' final lessons learnt reports. The analysis advances the dynamic process of timely engaging and disengaging external stakeholders in a context not previously explored in the literature related to dementia-friendly environments. Eight recurring practices and six rationales, the latter characterized by their temporal dimension, are presented in a processual model of stakeholder management.